Efektywność gospodarowania w socjalizmie - Rössler, Hans; Seidel, Helmut (Wydział Prawa i Administracji UAM, 1983)
The article is devoted to the discussion of some problems of effectiveness of management in socialism. The authors attempt at precising a question of management effectiveness measurements, indicating at previous not satisfactory, one sided presentation of that issue in literature. They define notions of economic and socio-economic effectiveness, presenting their interrelations and differences. Effectiveness of management can decisivelly effect a level and structure of consumption, but simultaneously a feedback is observed and conditions of social reproductions are under the impact of consumption. On account of this phenomenon, the authors analyse many-sided relations of consumption and effectiveness of management. On the example of the GDR economy they present problems of rational fullfillment of consumption needs from the viewpoint of choosing effective productional technics. Difficulties in the assessment of consumption effectiveness are indicated, as well as the necessity of further development of that sphere of management.
Effectiveness of management in socialism